Evaluation of Morphologic Dimensions of Humulus Appendix of Pterygoid Plate using Cone Beam Computed Tomography (CBCT) in Ahvazian patients, Iran - Saadi , Zahra; Sharifi Shushtari , Sanaz; Hashemi Ashtiani , Alireza; Tayebi, Ali (Galen Medical Journal, 2025)
Background: Today, CBCT has found a special place in dentistry due to the high quality and accuracy of images and providing information, and its use is increasing. With its help, we can examine many parts of the anatomy that are difficult to evaluate. The purpose of this study is to investigate the morphological dimensions of the humulus of the pterygoid appendage using cone beam computed tomography (CBCT). Materials and Methods: In this retrospective study, the statistical population was the imaging reccords of patients who referred to the radiology department of Ahvaz Dental School for CBCT of the upper jaw, whose values were stored in the NNT software. The size of the humulus (length and width) and its slope in the coronal and axial sections of the images were evaluated by two oral and maxillofacial radiologists. The results were analyzed using SPSS software version 22. Results: Eighty pterygoid hamuli from 38 males and 42 females (age 26–64 years, mean 43.18 ± 11.57) were analyzed. No significant gender differences were observed in length (p = 0.096), width (p = 0.300), axial angle (p = 0.067), or coronal angle (p = 0.102). Age-related comparisons revealed significant variation: hamular length and width increased in the 31–40 and >51 year groups versus <30 years (p = 0.022–0.031), axial angle was higher in 31–40 and >51 year groups (p = 0.003–0.006), and coronal angle increased in 31–40 and >51 year groups (p = 0.047–0.049). Conclusion: These findings indicate gradual morphometric changes with age, independent of gender. The length of PH increases with age and then decreases. While the width increases with age. There was no significant difference between length and width measurements in men and women. These findings help to diagnose vague pains in the oropharynx region related to the altered morphology of PH.